Thermochemical processes : principles and models - Alcock, C. B. (Butterworth-Heinemann, 2001)
Today the study of materials is concerned with the underlying thermodynamic and chemical processes involved in the manufacture and processing of a wide range of materials - metals, ceramics, semi-conductors, plastics and composites.For the first time, this book provides a quantitative description and examples of the application of physical chemical concepts to the processing and degradation of metallic and other inorganic materials, from the atomic scale to the analysis of industrial processes. Thermochemical Processes: Principles and Models deals with processes dominated in turn by the gas ph.